DARIDOREXANT IN THE TREATMENT OF INSOMNIA IN ELDERLY PATIENTS WITH COMORBIDITIES - Zofia Hałabuda; Kornelia Rynkiewicz (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and objective: Insomnia is one of the most prevalent sleep disorders in the adult population, thereby new methods of pharmacological treatment ought to be analyzed. Current novelty in insomnia treatment is daridorexant, a representative of the dual orexin receptor antagonist (DORA). Given that, the orexin system becomes overactive with age, explaining sleep of lower quality and quantity observed in older population, it is worth analysing the effect of the dual receptor antagonist (DORA) on the insomnia issue in older adults, and whether it proposes a safer choice among the existing pharmacological possibilities. Review methods: A comprehensive literature review was conducted, analyzing studies from the PubMed database of articles published between 2020 and 2025. Brief description of the state of knowledge: Insomnia treatment is based on both non-pharmacological and pharmacological methods. While among non-pharmacological methods cognitive-behavioral therapy is the one recommended, the choice of proper pharmacotherapy can impose more difficulties. The most commonly used medications, nonbenzodiazepine sedative hypnotics, lead to serious adverse effects and impose a risk of dependency. Daridorexant, a medication of proven efficacy, may propose a safer alternative, and furthermore, a more effective one. Summary: In this review, we decided to analyse the existing literature to present the current state of knowledge on the above-mentioned issue with a perspective of the future of this branch of medicine.